The Proposal of Constitutional Complaint for the Indonesian Constitutional Court - Nindry Sulistya Widiastiani (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
The research focuses on the proposal of a Constitutional Complaint for the Indonesian Constitutional Court. The background causes of the constitutional weakness to protection and fulfilment of constitutional rights, especially the absence of a Constitutional Complaint mechanism. Research methods used normative legal research methods with statutory, analytical, and case approaches. The study results show that legal thinking, including an embodiment of the values of constitutionalism in the rule of law of Pancasila, complements a checks and balances system, the basis for protecting fundamental rights, and aims to realize good governance. There are several steps/ methods to giving this authority, amendments to the 1945 Constitution, non-original interpretations, and revision of the Constitutional Court Act. Several objects of dispute are the Court’s verdict, the problems of interpreting the 1945 Constitution and law by a state official, People Consultative Assembly decisions, and others.